THE RELATIONSHIP BETWEEN WORK MOTIVATION AND NURSE PERFORMANCE - Oktavian Rau; Sabina Gero; Witri Hastuti (Jurnal SMART Keperawatan, 2025)
Introduction: Work motivation is an important factor that influences nurses' performance in providing healthcare services. Performance relates to individual behavior that is carried out intentionally and benefits both individuals and organizations in the form of work results that meet specific standards regarding the quality of actions performed. Objective: This study aims to analyze the relationship between work motivation and nurses' performance at Anugerah Regional General Hospital in Tomohon City. Method: The research method used is a quantitative approach with a sample size of 86 individuals, selected using purposive sampling. Data collection was conducted through a modified questionnaire from previous studies, and statistical analysis was performed using the chi-square test. Result: There is a significant relationship between work motivation and nurses' performance, with a p-value of 0.004. Conclusion: High work motivation positively contributes to improving nurses' performance, including aspects such as patient care, time efficiency, and professional responsibility. That hospital management continue to develop strategies to enhance work motivation to support the optimization of nurses' performance and improve the overall quality of healthcare services.